Role of Myocardial Fibrosis in Hypertrophic Cardiomyopathy: A Systematic Review and Updated Meta-Analysis of Risk Markers for Sudden Death - Bittencourt,Marcelo Imbroinise (2019)
Abstract Background: Hypertrophic cardiomyopathy (HCM) is associated with sudden death (SD). Myocardial fibrosis is reportedly correlated with SD. Objective: We performed a systematic review with meta-analysis, updating the risk markers (RMs) in HCM emphasizing myocardial fibrosis. Methods: We reviewed HCM studies that addressed severe arrhythmic outcomes and the certain RMs: SD family history, severe ventricular hypertrophy, unexplained syncope, non-sustained ventricular tachycardia (NSVT) on 24-hour Holter monitoring, abnormal blood pressure response to exercise (ABPRE), myocardial fibrosis and left ventricular outflow tract obstruction (LVOTO) in the MEDLINE, LILACS, and SciELO databases. We used relative risks (RRs) as an effect measure and random models for the analysis. The level of significance was set at p < 0.05. Results: Twenty-one studies were selected (14,901 patients aged 45 ± 16 years; men, 62.8%). Myocardial fibrosis was the major RISK MARKER (RR, 3.43; 95% CI, 1.95-6.03). The other RMs, except for LVOTO, were also predictors: SD family history (RR, 1.75; 95% CI, 1.39-2.20), severe ventricular hypertrophy (RR, 1.86; 95% CI, 1.26-2.74), unexplained syncope (RR, 2.27; 95% CI, 1.69-3.07), NSVT (RR, 2.79; 95% CI, 2.29-3.41), and ABPRE (RR, 1.53; 95% CI, 1.12-2.08). Conclusions: We confirmed the association of myocardial fibrosis and other RMs with severe arrhythmic outcomes in HCM and emphasize the need for new prediction models in managing these patients.